Seasonality of Respiratory Viral Infections: Will COVID-19 Follow Suit? - Audi, Amani; AlIbrahim, Malak; Kaddoura, Malak; Hijazi, Ghina; Yassine, Hadi M.; Zaraket, Hassan (Frontiers in Public Health, 2020)
Respiratory viruses, including coronaviruses, are known to have a high incidence of infection during winter, especially in temperate regions. Dry and cold conditions during winter are the major drivers for increased respiratory tract infections as they increase virus stability and transmission and weaken the host immune system. The novel severe acute respiratory syndrome coronavirus -2 (SARS-CoV-2) is associated with severe illness and an unprecedented devastating economic burden. The world is currently experiencing the first wave of the pandemic, which will likely be followed by multiple and more severe waves. Even though tropical regions are suffering from a high COVID-19 pandemic burden, virus transmission has been more aggressive in the temperate regions where winter is prevailing. This indicates that cold and dry conditions might promote SARS-CoV-2 infections. Based on our previous knowledge about the seasonality of respiratory viruses and the recent studies about stability and transmission of SARS-CoV-2, we speculate that the virus might mimic the other respiratory viruses and wane during summer due to warmer and more humid weather.